Limitation between Sharia and law A comparative jurisprudence study - Al-Nasseri, سهام علي حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The statute of limitation is a legal system in which time is an essential element. Most of the man-made laws adhere to it. Law commentators consider that the statute of limitations is the source of the Roman law، which is considered the basis for the laws of the Middle Ages in Europe، and the subsequent modern laws، such as the French law.